Anaplastic mammary carcinoma in a captive jaguar (Panthera onca) - Tochetto, Camila; Marietto Gonçalves, Guilherme Augusto; Zanoni, Diogo Souza [UNESP]; Pereira, Renato Lemos; de ARAÚJO, Gisele Torres Clímaco; Rocha, Renan Mori; Ulsenheimer, Bruna Carolina; Tonin, Alexandre Alberto (FapUNIFESP (SciELO), 2023)
A captive female of jaguar (Panthera onca), 12 years old, presenting an 8-day history of anorexia and lethargy, died in its enclosure in Manaus (Amazonas, Brazil). The necropsy revealed an abdominal multinodular ventral plaque into the mammary region. Additionally, in several locations of the subcutaneous tissue, there were multiple metastatic nodules of firm texture. Metastases were also observed in the lymph nodes, heart and lungs. The immunohistochemistry results revealed the cytoplasmic staining for cytokeratin on neoplastic cells, mild staining (+) for E-cadherin, moderate staining (++) for estrogen and progesterone receptors, and about 50 to 70% of staining for Ki-67. The neoplastic cells were negative for vimentin staining. Therefore, the histopathological examination led to a diagnosis of metastatic anaplastic mammary carcinoma, which is an unusual condition in wild felines.
Carcinoma mamário anaplásico em uma onça-pintada (Panthera onca) criada em cativeiro
Keywords: Amazon; Felidae; neoplastic disease; wild feline